Optimalisasi Pendistribusian Zakat dalam Meningkatkan Kesejahteraan Mustahik di BAZNAS Kabupaten Madiun - Rochmawati, Ika; Humaidi, Muchtim (Institut Agama Islam Negeri Ponorogo, 2023)
Zakat is a potential resource for Muslim development. There are many zakat management institutions. However, many of them are still not optimal in their distribution. One of them is BAZNAS of Madiun Regency. This research focused on three things. They are the optimization of zakat distribution, the supporting and the inhibiting factors of zakat distribution, and the impact of zakat distribution to improve community welfare in BAZNAS of Madiun Regency. The type of research used is field research. This study uses a qualitative approach. The research was performed at BAZNAS of Madiun Regency. The data was collected using interviews, observations, and interview techniques. Based on the results, the implementation of zakat distribution is still not best shown by the uneven distribution of zakat. There are still people from the ashnaf groups who have not received zakat. But BAZNAS of Madiun Regency only gave zakat to 20 mustahik to each village. The supporting factor in improving mustahik welfare at BAZNAS of Madiun Regency is its programs that are attractive to the community. In addition, BAZNAS of Madiun Regency and the local government established a good relationship. It demonstrates the professionalism of Madiun Regency BASNAS human resources. The inhibiting factors are the lack of supervision, guidance, and evaluation from BAZNAS of Madiun Regency regarding zakat distribution. Coordination between BAZNAS of Madiun Regency and the local government experienced human errors. And there is road damage to access some of mustahik’s houses. The impact of zakat distribution on the mustahik welfare at BAZNAS of Madiun Regency is still less effective as not all mustahik are already able to develop their businesses. Zakat merupakan salah satu sumber potensi pembangunan umat muslim. Banyak lembaga pengelola zakat, tetapi tidak sedikit yang belum optimal dalam pendistribusiannya. Salah satunya adalah BAZNAS Kabupaten Madiun. Penelitian ini difokuskan pada tiga hal, yaitu, optimalisasi pendistribusian zakat dalam meningkatkan kesejahteraan masyarakat, faktor-faktor pendukung dan penghambat pendistribusian zakat dalam meningkatkan kesejahteraan masyarakat, dan dampak pendistribusian zakat di BAZNAS Kabupaten Madiun. Jenis penelitian yang digunakan, yaitu penelitian lapangan. Penelitian ini menggunakan pendekatan kualitatif. Penelitian dilakukan di BAZNAS Kabupaten Madiun dengan teknik pengumpulan data menggunakan wawancara, observasi, dan wawancara. Berdasarkan hasil analisis data yang telah dilakukan menunjukkan bahwa dalam pelaksanaan pendistribusian zakat masih belum optimal. Hal ini ditunjukkan dengan pendistribusian zakat yang masih belum merata. Masih terdapat masyarakat yang termasuk ke dalam golongan 8 ashnaf yang belum mendapatkan zakat. Pada praktiknya, BAZNAS Kabupaten Madiun hanya memberikan zakat kepada 20 mustahik untuk tiap desa. Faktor-faktor pendukung dalam meningkatkan kesejahteraan mustahik di BAZNAS Kabupaten Madiun, yaitu program-program BAZNAS Kabupaten Madiun yang menarik bagi masyarakat. Selain itu, terjalinnya hubungan yang baik antara BAZNAS Kabupaten Madiun dengan pemerintah desa menggambarkan profesionalitas SDM BASNAS Kabupaten Madiun. Sementara itu, faktor-faktor penghambatnya adalah kurangnya pengawasan, pembinaan, dan evaluasi dari BAZNAS Kabupaten Madiun dalam hal pendistribusian zakat; koordinasi antara BAZNAS Kabupaten Madiun dengan pemerintah yang mengalami human error; dan kerusakan akses jalan menuju ke beberapa rumah mustahik. Dampak pendistribusian zakat terhadap kesejahteraan mustahik di BAZNAS Kabupaten Madiun dinilai kurang efektif sebab tidak semua mustahik telah mampu mengembangkan usahanya.